2012
DOI: 10.2739/kurumemedj.59.61
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Procedures, Complications, and Prognosis for Gastric Cancer in the Very Elderly (^|^gt;85): A Retrospective Study

Abstract: Summary: Many elderly individuals suffer from reduced functioning of major organs with cardiovascular and respiratory system comorbidity. Consequently, surgical stress and postoperative complications can be fatal. We investigated whether gastrectomy can safely improve the prognosis in very elderly (>85 years) patients with gastric cancer. We compared the clinical and pathological features of patients 85 years and older (Group A) with those 80-to 84-year-old (Group B) who underwent gastrectomy. We also compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
4
2
0
Order By: Relevance
“…More importantly, we found that within the group of elderly patients age ≥80 yrs, surgery could significantly improve OS, especially for early stage patients with resectable proximal gastric carcinoma. This finding is consistent with previous reports focusing on overall elderly patients with gastric cancer, regardless of tumor sites [17,29,30]. Moreover, the survival benefit of surgery was observed in both healthy and less healthy patients with certain comorbidities (CDCI ≥1), indicating that age-associated comorbidities should not be considered as absolute contraindication for surgery [13,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, we found that within the group of elderly patients age ≥80 yrs, surgery could significantly improve OS, especially for early stage patients with resectable proximal gastric carcinoma. This finding is consistent with previous reports focusing on overall elderly patients with gastric cancer, regardless of tumor sites [17,29,30]. Moreover, the survival benefit of surgery was observed in both healthy and less healthy patients with certain comorbidities (CDCI ≥1), indicating that age-associated comorbidities should not be considered as absolute contraindication for surgery [13,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, we found that within the group of elderly patients age ≥80 yrs, surgery could significantly improve OS, especially for early stage patients with resectable proximal gastric carcinoma. This finding is consistent with previous reports focusing on overall elderly patients with gastric cancer, regardless of tumor sites [17,29,30]. Moreover, the survival benefit of surgery was observed in both healthy and less healthy patients with certain comorbidities (CDCI ≥1), indicating that age-associated comorbidities should not be considered as absolute contraindication for surgery [13,31,32].…”
Section: Discussionsupporting
confidence: 91%
“…More importantly, we found that within the group of elderly patients age ≥80 yrs, surgery could significantly improve OS, especially for early stage patients with resectable proximal gastric carcinoma. This finding is consistent with previous reports focusing on overall elderly patients with gastric cancer, regardless of tumor sites[17, 29,30]. Moreover, the survival benefit of surgery was observed in both healthy and less healthy patients with certain comorbidities (CDCI ≥1), indicating that age-associated comorbidities should not be considered as absolute contraindication for surgery [13,31,32].…”
Section: Discussionsupporting
confidence: 91%